(untitled) (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
This research study investigated the relationship between employee participation in decision making, emotional intelligence and employee job satisfaction, and the extent to which emotional intelligence moderated the relationship between employee participation in decision making and employee job satisfaction. The study was conducted on 383 banking sector employees working in J&K, India. Results posited that employee participation in decision making and emotional intelligence had significantly positive influence on employee job satisfaction, with emotional intelligence having higher impact. Emotional intelligence also moderated the relationship between employee participation in decision making and employee job satisfaction. The study implications and limitations were discussed.